Research and publication on the oil hydrogenation process in margarines using catalysts (Research, Society and Development, 2021)
The hydrogenation process of oils and fats is a chemical process resulting from simultaneous reactions, which requires the presence of a reaction catalyst. The use of a metal in the hydrogenation process contributes to the acceleration of the reaction, provided that factors such as adequate pressure and temperature are employed. The available bibliographies researched on Google Scholar point to nickel as the element most used as a reaction catalyst in the food industry, mainly in the process of hydrogenation of oils and fats to obtain the margarine product. As it presents the characteristics of a non-limited resource and, consequently, low cost and food safety at the end of the hydrogenation process, nickel continues to be the industry's first option for the function of catalyst. Thus, the objective of the present study will be to carry out a literary search on the hydrogenation process of oils and fats and the use of reaction catalysts, from works published in the last five years and available through the Google Scholar platform, as it is a process widely used in the food industry and mainly for the manufacture of margarines.